Thermal properties of cement-based materials: Multiscale estimations at early-age. (March 2018) - Honorio, Tulio; Bary, Benoit; Benboudjema, Farid
Abstract: The prediction of the thermomechanical response of cement-based materials depends on the adequate determination of the thermal properties. At early-age, these properties depend on the evolution of the microstructure due to hydration processes and the multiscale nature of CBMs. In this paper, the heat capacity, the thermal conductivity and the coefficient of thermal expansion of cement-based materials are estimated by means of analytical homogenization. Estimates at the scales of cement paste, mortar and concrete are provided. At cement paste scale, the evolution of the volume fractions of clinker minerals and hydrates are taken into account. Interface Transition Zone (ITZ) is considered at mortar scale. A discussion about the effective properties of the "pore phase" and C-S-H as well as their influence on the effective behaviour is provided. A formulation accounting for the mechanical coupling in the determination of the heat capacity is used. Finally, the model estimations prove to be consistent with experimental data from the literature. Highlights: Early age thermal properties estimated by means of homogenization techniques. Effects of thermal expansion on heat capacity are negligible at cement paste scale. ITZ plays an important role on thermal conductivity.